(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In the modern world, special importance is given to the development of social infrastructure, including the growth of trade and service complexes at the agglomeration level. Today, developed countries are actively seeking measures to enhance socio-economic relations and to utilize agglomeration highways more effectively in this field. Particular attention is paid to the implementation of comprehensive projects aimed at forming agglomeration trade complexes connected to highways, as well as the reconstruction of existing trade centers to meet modern standards and address current needs. Scientific research conducted around the world places special emphasis on the rational use of trade and service infrastructure facilities along highways (trade and service complexes), architectural solutions for trade complexes both in city centers and on their outskirts, and the improvement of urban planning methods for the optimal placement of trade facilities. Many countries are working on the development of design standards that are aimed at practical implementation by design organizations [1,2,3,4,10,12,14]. In this direction, developed countries such as the United States and Turkey have made significant progress in analyzing and studying large trade complexes, such as Eastland in the Detroit City area and the Grand Bazaar in Istanbul. A priority focus is the study of the architectural and planning features of new, modern types of trade and service complexes.